Komunikasi Interpersonal Pelatih-Atlet untuk Peningkatan Motivasi Berprestasi pada Pelatihan Bola Basket Universitas - Januke, Marisa; Jati, Rocky Prasetyo (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This article examines the interpersonal communication strategy between coaches and men's basketball athletes at Budi Luhur University to increase achievement motivation. The focus of the discussion is directed at the communication model used, the role of interpersonal communication, and obstacles that arise in the interaction between coaches and athletes. The qualitative approach is used in in-depth interviews with the coach and relevant athletes and direct observations of the training dynamics. The analysis results show that the trainer applies an interactive and transactional communication model, including direct instructions, evaluation, and effective feedback. It was also found that interpersonal communication elements such as openness, empathy, emotional support, positive attitudes, and equality played a crucial role in forming strong and conducive interpersonal relationships for athletes' achievements. However, there are still challenges in the form of inequality between some athletes who need further attention through open and transparent communication from the coach. Overall, effective interpersonal communication contributes significantly to increasing achievement motivation, the quality of relationships in the team, and achieving optimal sports achievement goals.